BASES ELECTROFISIOLÓGICAS DE LA ESTIMULACIÓN CARDÍACA / Electrophysiological basis of cardiac pacing - Ginner Odorico Rizo Rivera; Raimundo Carmona Puerta (CorSalud, 2009)
The search for a physiological cardiac pacing has made the functioning of the pacemakers increasingly complex. This complexity ranges from the detection of the cardiac signal, its fitting-outand the response of the pacemaker by means of algorithms, to the electrical pacing of the heart. It is a must for us, as professionals devoted to cardiology, to know the basic principles of this process.The electrophysiological basis of electrical cardiac pacing is treated in this article, trying to achieve a general understanding of it, and in consequence facilitating a better comprehension of a topic that we hear or deal with, over and over, in our medical practice.